Kaj morajo načrtovalci novih proizvodov vedeti o tehniki spajanja? - Tušek, Janez (Kovine zlitine tehnologije, 1997)
The aim of the paper is to show some basic characteristics of joining technique for materials, which are often forgotten by designers of new welded products. In the first place basic and general requirements regarding welded products, which should be fulfilled by the weld, the welded joint and the final welded product fit for use respectively, are stated. Factors making part of the manufacturing process for the welded product and which may be affected in order to obtain optimum results are shown schematically as well. Some of these factors are material selection, welding procedure selection, including measures taken before, during and after welding, structure plan, i.e. product design, and skilled and certified personnel who guarantee high quality of welding operation.
Keywords: varjenje; varivost; spajanje; materiali; zvarni spoji; postopki